FENOMENA JASTIP DALAM PANDANGAN EKONOMI ISLAM: STUDI PADA JASTIP SOP BUAH IRINE - Adhi Purba, Ilyas (Politeknik Bisnis Indonesia, 2025)
The phenomenon of entrustment services (jastip) is a practice that is growing rapidly in modern society, especially in the digital era and social media. Jastip allows someone to buy goods entrusted to them from a certain place and receive compensation for these services. This research aims to examine the practice of jastip irine fruit soup in Gresik, East Java. This research uses a descriptive qualitative approach with data collection techniques in the form of observations and supporting documentation from social media and transactions carried out. The results of this research explain that in the Islamic economic view it is categorized as wakalah bil ujrah (wage representation). This practice is legal as long as it meets sharia principles, such as consent (ridha), clarity of contract, price transparency and does not contain gharar (unclarity), usury or tadlis (fraud).